An epidemiological study on association of maternal stress, anxiety and depression with low birth weight in a tertiary care hospital of Kolkata, West Bengal - Mohanta, Munu; Bagchi, Abantika; Mukherjee, Mahul; Dwivedi, Malvika (International Journal Of Community Medicine And Public Health, 2025)
Background: Low birth weight (LBW) is a significant public health problem globally. In India every 3rd newborn is a LBW contributing to about 40% of the global burden. Maternal stress, anxiety and depression have been shown to impact on the progress and outcome of pregnancy, especially those related to LBW. This study was done to find the psychological factors associated with LBW among babies delivered in a tertiary care hospital in Kolkata. Methods: It was a cross-sectional institution based observational study conducted from November 2016 to October 2018 among 410 postnatal mothers in the postnatal ward of the department of obstetrics and gynaecology, medical college, Kolkata, West Bengal. Data was obtained by interview method along with record analysis (medical and hospital records). Dependent variable was LBW (<2.5 kg). Ethical clearance was obtained from local ethics committee of all India institute of hygiene and public health Kolkata and medical college, Kolkata. Results: Out of 410 babies, 112 (27.3%) were LBW. Out of 112 LBW babies, 59 (52.7%) were pre-term (<37 weeks); 51 (45.5%) were term (37-42 weeks) and 2 (1.8%) were post-term (>42 weeks). Among the mothers, 22.0% had anxiety, 17.1% had depression and 65.4% had stress during pregnancy. Conclusions: In this study, association of LBW with anxiety, depression, both anxiety and depression, stress in mothers during pregnancy was not found. However, minimizing stress and having sufficient sleep during pregnancy is recommended.